The Role of Competitive Advantage Mediates Entrepreneurial Orientation and Product Innovation on Marketing Performance - Sudirjo, Frans; Sulistiyani, Sulistiyani (Politeknik APP Jakarta, 2023)
The purpose of this study is to analyze the entrepreneurial orientation partially affects competitive advantage. The entrepreneurial orientation and product innovation simultaneously affect competitive advantage, and competitive advantage partially affects marketing performance. This study uses saturated sampling with a total sample of 107 lubricating oil managers in the city of Semarang. The data analysis technique in this study uses path analysis techniques, with the help of the Statistical Package for Service Solution (SPSS) program 22. The results show that entrepreneurial orientation partially has a positive and insignificant effect on competitive advantage, product innovation partially has a positive and significant effect on competitive advantage, entrepreneurial orientation and product innovation simultaneously have a positive and significant effect on competitive advantage, competitive advantage partially affects marketing performance.